REFORMATION OF HIGHER EDUCATION IN EUROPE: ESSENTIAL BENCHMARKS AND INSIGHT IN REFORMING THE NATIONAL EDUCATION SYSTEM - Bileviciute, Egle; Zaleniene, Inga (European Scientific Journal, ESJ, 2013)
The main purpose of article is to analyze the new situation in higher education in Lithuania in globalization context. Higher education has long been recognized as contributing to the social, cultural and intellectual life of society by improving the level of human capital. Processes of globalization, knowledge society development changed the conditions for universities and brought for home management the new requirements. In many countries of the world is increasing rapidly the number of students. This trend is characteristic for Lithuania too. The number of interested groups - the students themselves, employers, public authorities, and the general public rears the new requirements for universities’ management. Knowledge and technology has become a major economic and social development factor. Competition in higher education, new challenges have arisen due to the fact that the university has begun reforming its management. The European Council considers that higher education institutions have a wealth of scientific and educational potential, but it is not sufficiently exploited for economic governance processes, society and business. Managerial take over the business management techniques, leadership, payback criteria, investments, marketing strategies have become commonplace in higher education. The university management efforts to include more stakeholders, highlights the cooperation between the public and business value. Universities have become immediate the part of the national innovation system, and able to contribute significantly to the edge of economic progress. Lithuanian high-education institutions also received a substantial change. The article presents the analysis of the development of higher education in Lithuania according European trends.